Improving trust and reciprocity in agricultural input markets: A lab-in-the-field experiment in Bangladesh - de Brauw, Alan; Kramer, Berber (International Food Policy Research Institute, 2022)
Adoption of high-quality yet more expensive agricultural inputs remains low, in part because most inputs are experience goods: before purchase, buyers observe only price—not quality—providing sellers with opportunities to cheat on quality. Our lab-in-the-field experiment in Bangladesh replicates markets for such inputs, with input retailers (sellers) choosing price and quality, and farmers (buyers) choosing from which seller to purchase inputs. We analyze market behavior, including buyers’ trust and sellers’ reciprocity, and study the effects of buyer-driven accreditation and loyalty rewards for accredited sellers of high-quality products. Trust and reciprocity remain low: Sellers provide mostly low-quality products, and buyers reveal low demand for more expensive, high-quality inputs. Accrediting sellers when their buyers are satisfied leads to higher input quality and more repeat purchases, but only when combined with loyalty rewards, because buyers’ quality signals are weak and do not incentivize sellers to change their behavior. We conclude that small incentives are effective at improving seller behavior, but this behavior change does not necessarily enhance quality signals and farmer welfare.